Resveratrol improved atherosclerosis by increasing LDLR levels via the EGFR-ERK1/2 signaling pathway - Dandan Hu; Litian Wang; Lin Qi; Xiangxuan Yang; Yamin Jin; Huailiu Yin; Yewei Huang; Jun Sheng; Xuanjun Wang (Lipids in Health and Disease)
Abstract Background and aims Atherosclerosis (AS) is a complex and chronic vascular disease and elevated low-density lipoprotein cholesterol (LDL-C) level is one of its primary causative factors. As a key surface receptor, low-density lipoprotein receptor (LDLR) plays an essential role in LDL-C clearance. Resveratrol (RSV) has emerged as a promising compound for investigating potential therapeutic targets for AS due to its ability to lower cholesterol, reduce endothelial anti-inflammatory and suppress vascular smooth muscle cell proliferation. This study explored the effects of RSV on AS through upregulating LDLR and analyzed the mechanism through a combination of in vivo and vitro experiments. Methods HepG2 cells were exposed to varying concentrations of RSV. The effects of RSV on LDLR expression and cholesterol uptake were analyzed by western blot, RT-qPCR and DiI-LDL uptake assay. In vivo, C57BL/6J ApoE−/− mice were used and the experimental groups were treated with RSV, Lovastatin and Gefitinib. Plaque formation in the arteries and aortic roots was assessed by Oil Red O staining and plaque stability was evaluated using Hematoxylin-Eosin (H&E) and Elastic Van Gieson (EVG) staining. Western blot, RT-qPCR and immunohistochemical staining were employed to analyze the expression of LDLR in the livers of mice. Results RSV significantly enhanced the stability of LDLR mRNA and promoted LDLR protein expression. The inhibition experiments of EGFR signaling pathway (Cetuximab and Gefitinib) demonstrated that the efficacy of RSV was markedly weakened when this signaling pathway was inhibited. It indicated that RSV modulated LDLR gene expression by activating EGFR-ERK1/2 pathway. In ApoE−/− mice, RSV notably reduced arterial plaque formation, improved plaque stability and increased hepatic LDLR expression. Conclusion This study elucidated the mechanism by which RSV upregulates LDLR gene expression through activating EGFR-ERK1/2 signaling pathway. In vivo experiments demonstrated its efficacy in reducing arterial plaque formation and stabilizing existing plaques. These results further indicated that RSV held potential therapeutic value for ameliorating atherosclerosis and cardiovascular diseases. Collectively, these findings provided novel theoretical support for RSV’s potential role in cardiovascular therapy.